Les opérations de maintien de la paix des Nations unies, une géographie politique appliquée - André-Louis Sanguin (L'Espace Politique)
The UN peacekeeping operations make up a not very scrutinized issue of political geography. A theoretical assessment is proposed about the relationships between peace, geography and United Nations as well as the spaceness of peacekeeping operations. The paper shows a new typology of the UN peace spaces : interposition, survival, covering, governance, marking. The conclusion identifies some observable trends and conceivable prospects for a political geography of peace.